(untitled) (Bulletin of Armenian Libraries, 2023)
In this talk, I suggest five initiatives for libraries in Armenia to promote reading. A circle-shaped mother-child reading room, where the child can play with toys and books while the mother reads. Target audience for this project are mothers with children under 3. • Psychologist’s office for library users and personnel (with registration). • During “Library Night” famous literary heroes (performance by actors) will visit the library, inspire readers, and take part in theatrical events. Library users will have a chance to read at night in the library. • Screenings of films based on famous books once a month. • Literary discussions based on previously read literature.